Processamento de aço inoxidável dúplex por extrusão em canal angular - Farias, Fernanda Aparecida (2009)
A duplex stainless steel with austenitic–ferritic structure, type S32205/S31803 was submitted to equal channel angular pressing, whose is based on very severe plastic deformation, at relatively low temperature, with no change in the dimensions along transversal section of the material. The processed material was heat treated at 1000° and 1200°C during 7.5, 15, 30 and 60 minutes, in order to evaluate the recovery aspects and recrystallization steps of the severely deformed duplex steel. The die was manufacturing from SAE 1045 steel (cemented, quenched and annealed) and heat treated and the plungers from tool steel. The extrusions were conducted at room temperature, using a universal type mechanical test machine, according three different pressing speeds: 1.5, 6.0 and 12.0 mm/min. The processing stress increase continuously during extrusion by friction forces between sample and die walls and very high pressing stress level was reached. The results show the increase of stress according to increase of speed processing. For 1,5 mm/min processing speed, the second pass could be done with maximum reached stress close to 3GPa. The friction forces promoted a very heterogeneous deformations process along the samples sections with increase of hardness from 257HV (start material) to 575HV (highest deformed point). This effect was observed by grains morphology and orientations changes after processing and along the sample dimensions. In the as heat treated samples surfaces two distinct structures type formation was verified with small surfaces positioned with well defined angles near of 90° and 109° between itself. The region with 90° between surfaces show a lot of cubic form structure probably as a consequence of dislocation pile up annihilation on the surface of body-centered-cubic phase (ferrite). In this crystalline structure, the slip system occurs mainly in the {110} planes which have 90º between then. In another side, the slip planes of face-centered-cubic structure slip systems (planes {111}) make 109º angles between then and consequently, dislocation annihilation on the surface may result in structures with this angles on the austenite regions. Sample surface observations detected “roof like” morphology with a well defined near 109º structures which suggest the dislocation annihilation on austenite. Another structure detected on the sample surface was the cold induced martensite. The preliminary evaluation of recrystallization of some processed and treated samples, at 1000°C for 7,5, 15 and 30 minutes identified located points of recrystallization in the grain contours. With increase of the time of heat treatment from 7,5 to 15 minutes, increase of recrystallization nuclei was detected, whereas after treatment of 30 minutes verifies increase of the size of crystals formed without expressive increase of the number of nucleis.